(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
Background: Seasonal influenza is a widespread and highly contagious illness that can impact both the upper and lower respiratory tracts in individuals of all ages, predominantly during the winter months. The aim of this study was to evaluate public knowledge, attitudes, and practices relating to influenza and its influenza vaccination. Materials and Methods: A descriptive online cross-sectional survey was conducted over a 1-month, from September to October 2023. The survey targeted the population living in the Aseer region, Saudi Arabia, using convenience and snowballing sampling methods. Results: The table presents demographic and health-related data of the studied population. More than half of the participants (52.2%, 70 respondents) aged 25–34 years, 88% (n = 117) were male, 83.5% (n = 111) had university-level education (83.5%, n = 111), with post-graduate education at 3.8% (n = 5), 81.2% (n = 108) were city residents, and 53.4% had monthly income of 50,000–10,000 SAR. Large sector of the surveyed population (80.0%) had good knowledge about influenza while mall sector had poor knowledge 12%. Among the studied population, 63.91% had good attitude about seasonal influenza and its vaccine while 11.28% had bad attitude. Females exhibit a lower vaccination rate (25.00%) compared to males (63.25%). This gender difference was statistically significant (P = 0.004). Conclusions: The study showed a generally positive knowledge and attitude toward the seasonal influenza vaccine, with most respondents willing to receive it. However, awareness of potential side effects and severe reactions varies. Targeted interventions are needed to address lower vaccine acceptance.